Discordant tooth agenesis and peg-shaped in a pair of monozygotic twins: Clinical and molecular study - Lívia Azeredo Alves Antunes; Erika Calvano Küchler; Marcelo de Castro Costa; Leonardo Santos Antunes; José Mauro Granjeiro (Wolters Kluwer Medknow Publications, 2013)
The present report aimed to study an uncommon case of a pair of twins that presented a discordant dental phenotype. Family investigation, clinical, radiographic examination and molecular analysis were performed in both girls. Molecular analysis confirmed the monozygosity by deoxyribonucleic acid chip technology. One twin presented tooth agenesis in left upper lateral incisor and peg-shaped on the contra lateral side while the other twin had no dental alterations. The dental casts study employed digital caliper to compare morphological dimensions and showed alteration only in peg-shaped tooth. In conclusion, this study provide support that one or more mutated gene could cause discordances in dental phenotype in these monozygotic twins.